Community tourism as a form of empowerment for women : the case of the Mothers of Creation Route Western Cape South Africa - Boonzaaier, C.C. (University of Pretoria, 2019)
Dissertation (MHistorical and Cultural Sciences)--University of Pretoria, 2018.